Structural properties of cerium oxide doped zinc borotellurite glass / Hasnimulyati Laoding … [et al.] - Laoding, Hasnimulyati; Mohamed Kamari, Halimah; Shaari, Abdul Halim; Mansor, Ishak; Amat, Azuraida; Shahrol Nidzam, Nazirul Nazrin (Universiti Teknologi MARA Cawangan Pahang, 2021)
Zinc borotellurite glasses doped with CeO2 ({[[(TeO2)0.7(B2O3)0.3]0.7(ZnO)0.3]}1-xCeO2x where x = 0,1,2,3,4 and 5 mol%) were prepared using melt-quenching technique. The effect of cerium oxide was investigated by studying the structural properties of the glass system. Results showed that the density of glasses increased while the molar volume decreased with the addition of CeO2 from 1 until 5 mol%. The increment in density could be attributed to the higher molecular weight of cerium oxide while the reduction in molar volume indicated the tightening effect that occurred in the glass network. Fourier Transform Infrared Spectroscopy (FTIR) analysis exhibited absorption bands for tellurite and borate network. After the deconvolution process, the band area for each structural unit in the glass network was calculated. The changes in the band area of TeO4 and BO4 were found to be independent to the composition of cerium oxide. The amorphous nature of the prepared glasses was confirmed using X-ray diffraction (XRD). The changes on all of the data were elucidated and related to the modifications in the structural network.